Reporting delays of chikungunya cases during the 2017 outbreak in Lazio region, Italy - Manica, Mattia; Marini, Giovanni; Solimini, Angelo; Guzzetta, Giorgio; Poletti, Piero; Scognamiglio, Paola; Virgillito, Chiara; della Torre, Alessandra; Merler, Stefano; Rosà, Roberto; Vairo, Francesco; Caputo, Beniamino (PLoS neglected tropical diseases, 2023)
Background Emerging arboviral diseases in Europe pose a challenge due to difficulties in detecting and diagnosing cases during the initial circulation of the pathogen. Early outbreak detection enables public health authorities to take effective actions to reduce disease transmission. Quantification of the reporting delays of cases is vital to plan and assess surveillance and control strategies. Here, we provide estimates of reporting delays during an emerging arboviral outbreak and indications on how delays may have impacted onward transmission. Methodology/principal findings Using descriptive statistics and Kaplan-Meyer curves we analyzed case reporting delays (the period between the date of symptom onset and the date of notification to the public health authorities) during the 2017 Italian chikungunya outbreak. We further investigated the effect of outbreak detection on reporting delays by means of a Cox proportional hazard model. We estimated that the overall median reporting delay was 15.5 days, but this was reduced to 8 days after the notification of the first case. Cases with symptom onset after outbreak detection had about a 3.5 times higher reporting rate, however only 3.6% were notified within 24h from symptom onset. Remarkably, we found that 45.9% of identified cases developed symptoms before the detection of the outbreak. Conclusions/significance These results suggest that efforts should be undertaken to improve the early detection and identification of arboviral cases, as well as the management of vector species to mitigate the impact of long reporting delays.